THE EPIDEMIOLOGY OF TEMPOROMANDIBULAR JOINT DYSFUNCTION IN WOMEN OF REPRODUCTIVE AGE IN CENTRAL ASIA: A REVIEW - Komiljon Iminov; Shukhrat Boymuradov (Scholars Digest Publishing, 2025)
Temporomandibular joint dysfunction (TMJD) is a prevalent orofacial pain condition with a higher burden among women of reproductive age, yet epidemiological data from Central Asian countries are scarce. This review addresses the prevalence, risk factors, and health system challenges of TMJD in women (approximately 15–49 years old) across Kazakhstan, Uzbekistan, Kyrgyzstan, Turkmenistan, and Tajikistan. Methods: Review was conducted following PRISMA guidelines for scoping reviews. Literature from 2010–2025 was searched in English and Russian via PubMed, Google Scholar, and WHO databases for epidemiological studies on TMJD in Central Asia. Global and regional data were extracted from World Health Organization reports and peer-reviewed studies to contextualize findings. Key themes (prevalence, regional patterns, risk factors including hormonal influences, diagnostic issues, and health system factors) were synthesized qualitatively. No new human subject’s data were collected.
Keywords: Temporomandibular disorders; epidemiology; Central Asia; women’s health; reproductive age; prevalence; risk factors; hormonal influences; public health.